Structural and spectroscopic characterization of 4-(3-methyl-3-phenylcyclobutyl)-2-(2-propylidenehydrazinyl)thiazole: A combined experimental and DFT analysis - Sen, Fatih; Dincer, Muharrem; Cukurovali, Alaaddin (Pergamon-Elsevier Science Ltd, 2015)
We investigated the structural and spectroscopic properties of the title compound by means of experimental and DFT quantum chemical methods. The crystal structure of compound was brought to light by single crystal X-ray diffraction method, and were characterized spectroscopically using FT-IR and NMR spectra. FT-IR spectrum in solid state was observed in the region 4000-400 cm(-1). The H-1 and C-13 NMR spectra were recorded in CDCl3 solution. The molecular geometry were those obtained from the X-ray structure determination was optimized using density functional theory (DFT/B3LYP) method with the 6-31G(d, p) and 6-31+G(d, p) basis sets in ground state. From the optimized geometry of the molecule, geometric parameters (bond lengths, bond angles, torsion angles), vibrational assignments and chemical shifts of the title compound have been calculated theoretically and compared with the experimental data. Although theoretical calculations were carried out in gas phase, no significant differences in these values. (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Cyclobutane; Thiazole; Density functional theory (DFT); X-ray diffraction; Frontier molecular orbital analysis (FMOs)